The Effect of Leadership Effectiveness and Islamic Work Motivation on Organization Performance with Islamic Work Ethics as a Moderating Variable - Nur Faliza; Ahmad Muktamar B.; Rachmadi Setiawan; Wiwit Agustina (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Organizational performance is a measure of the progress of an organization that shows how well an organization achieves its goals and the results of work achievements that have been achieved by employees in accordance with their functions and work in a certain period. This research was conducted aiming to determine the effect of leadership effectiveness and Islamic work motivation on organizational performance with Islamic work ethics as a moderating variable. This study uses quantitative techniques with primary data collection method questionnaires. The population in this study are all employees of Amil Zakat Institutions in Indonesia. The sampling technique used purposive sampling obtained by 210 respondents. The results showed that the work effectiveness of Islamic leadership and motivation had a significant effect on organizational performance, which means that the first and second hypotheses were accepted, while the Islamic work ethic was not able to moderate the influence of Islamic leadership and work motivation on organizational performance so that the third and fourth hypotheses were rejected. Keywords: Leadership Effectiveness, Islamic Work Motivation, Islamic Work Ethics, Organization Performance